Аналіз перспектив співробітництва українсько-польських промислових підприємств - Климова, Світлана Олегівна (НТУ "ХПІ", 2015)
У статті розглядаються перспективи кооперації українських і польських промислових підприємств. Оцінюються найбільш привабливі галузі промисловості з точки зору можливого співробітництва. Аналізується доцільність кооперації шляхом зіставлення швидкостей зміни середніх одноразових витрат (витрат, що мають інноваційний характер) і середніх умовно-постійних витрат (витрат, що не мають інноваційного характеру).

The cooperation possibilities of the Ukrainian-Polish industrial enterprises are considered in the article. The most attractive industry sectors in terms of possible cooperation are estimated. The expediency of cooperation by comparing the rates of change of the average one-off costs (costs with innovative character) and average conditional - constant costs (costs that don’t have the innovative character) is analyzed.
The analysis of the cooperation possibilities of the Ukrainian-Polish industrial enterprises
Keywords: кооперація; ефект масштабу виробництва; середні одноразові витрати; конкурентоспроможність підприємств; cooperation; industrial enterprises; competitiveness of enterprises